Treatment of Horizontal Canal Benign Paroxysmal Positional Vertigo: A New Rehabilitation Technique - D. Testa; G. Castaldo; C. De Santis; A. Trusio; G. Motta (The Scientific World Journal)
The aim of this study was to evaluate the effectiveness of a new technical variant applied to the Gufoni's manoeuvre, in the treatment of horizontal canal benign paroxysmal positional vertigo (HSC-BPPV). 87 patients with BPPV of HSC (55 women and 32 men), aged between 21 and 80 years, were randomized either to modified Gufoni's manoeuvre or to the Gufoni's manoeuvre. 93% of patients treated with modified Gufoni's manoeuvre was cured after the first treatment session, of which only 2% had a conversion into PSC-BPPV, while the Gufoni's manoeuvre led to a symptoms resolution in 88% of cases, of which 16% had a conversion into PSC-BPPV. Therefore, the modified Gufoni's manoeuvre shows the same effectiveness in the resolution of symptoms of Gufoni's manoeuvre, but it appears more effective than the latter to reduce the percentage of conversion of the HSC-BPPV into PSC-BPPV (χ2=6.13, P=0.047).